Counting Room Voices in the Farm Publisher-Reader-Advertiser Triad - Stephen A. Banning; James F. Evans (Journal of Applied Communications, 2004)
This study is part of a series that examines changing power relationships among commercial farm periodicals, their readers, and advertisers. The series focuses upon the health, vigor, and credibility of a complex information system in which the U.S. food enterprise and society in general have an important stake. Authors employed a “contractualist model” in which power requires mutual agreement by all parties. Two previous studies in the series identified concerns of farm periodical journalists and readers about advertiser-related pressures on editorial content. Through qualitative research methods, the study reported here examined related views among a sample of agricultural publishers and advertisers. Both groups expressed the most concern about the consolidation taking place among producers, marketers, and publishers, but they focused on different sectors. All three kinds of consolidation have the effect of giving the advertiser more power within the triad. Publishers and advertisers emphasized the need to maintain editorial credibility of commercial farm periodicals, acknowledged advertiser-related pressures, but shared a feeling that such pressures can be controlled and should not influence the independent stance of editorial content. They differed somewhat, however, in views on managing the editorial-advertising “wall.” Publishers also identified ways in which they are adapting, through diversification, to changing strategies of advertisers in an era of consolidation and new information technologies. By revealing perspectives of all partners in the triad, findings provide a useful staging point for interactions and understandings.